НЕТРАДИЦІЙНІ ФОРМИ ГАРМОНІЗАЦІЇ В СИСТЕМІ п ід г о т о в к и ВЧИТЕЛЯ МУЗИКИ (Педагогіка вищої та середньої школи, 2007)
This article is devoted to the analisis and the generalized experience of untraditional practice in the assimilation of harmony's course, the introduction of unstandard method in the system of training teacher of music.